Identificação de Plasmodium spp. em primatas neotropicais e em anofelinos em municípios da região de São Luís, estado do Maranhão, Brasil - Figueiredo, Mayra Araguaia Pereira [UNESP] (2015)
Malaria is a disease of greater impact on Public Health in tropical countries because of the high morbidity and mortality. Considering malaria as a zoonosis in which primates can act as reservoirs of species of Plasmodium that can infect humans lead us to conduct malaria studies in primates with unquestionable relevance. It is generally know that the distribution of human and primate malaria following the same distribution of Anopheles mosquitoes vectors, in this study we investigated the presence of Plasmodium spp. in neotropical primates and Anopheles in São Luís Island, Maranhão State, Brazil. Samples were blood neotropical primates CETAS-São Luís (n = 141) and wild life (n = 20) Private Reserve Sítio Aguahy, São José de Ribamar. Anopheles mosquitoes were captured in the same reserve (n = 380) and Mangalho site (n = 36), located in the Environmental Protection Area of the Maracanã, São Luís, totaling 54 pools. The primate blood samples were subjected to morphological, serological (IFA and ELISA-test) and molecular (qPCR and conventional PCR) to identify Plasmodium. The pools of mosquitoes were assayed by testing for molecular identification of Plasmodium. Five primates had positive slides (3.10%) with observation trofozoíticas forms. In IFA four primate serum samples sororreagiram against the antigen of P. malariae. Amplified Plasmodium sp. qPCR at 34.16% (55/161) of samples of primates. In conventional PCR 30.43% (49/161) were positive, 47 (47/49) for P. brasilianum/P. malariae and 2 (2/49) to P.simium/P. vivax. Were sequenced DNA samples from four primates which showed identity with P. malariae (n = 2), Plasmodium ZOOBH (n = 1) and P. falciparum (n = 1). Three pools of Anopheles were positive for Plasmodium in qPCR (3/54) and conventional PCR. The sequencing samples showed identity to P. falciparum (n = 1), P. vivax (n = 1) and Plasmodium ZOOBH (EF090276). Due to the continued and increasing encroachment to forests by ...